Pengkajian dan Penerapan Strategi Pemasaran Berbasis Nilai-Nilai Kebangsaan UUD 1945 Berdasarkan Teknologi IOT Dalam Industri MIGAS di Indonesia : Perspektif Kepatuhan Terhadap UU MIGAS - Edy Soesanto; Fiqry Raihan Algifary; Bagus Wicaksono (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research aims to analyze the use of Internet of Things (IoT) technology in the marketing strategy of the oil and gas industry in Indonesia, with a focus on aspects of compliance with applicable oil and gas laws and regulations. The use of IoT technology has brought significant changes in various industries, and the oil and gas sector is no exception. In this context, this research will investigate how IoT technology can be used in oil and gas marketing strategies to improve operational efficiency, supervision, and compliance with oil and gas law regulations in Indonesia. The importance of compliance with oil and gas law regulations cannot be separated from the broader legal framework, namely the 1945 Constitution of the Republic of Indonesia (UUD 1945). The 1945 a Constitution is the Indonesian constitution which establishes the basic principles of the state, including the management of natural resources, including oil and gas, which are in the national interest. In this research, the use of IoT technology in oil and gas marketing strategies will be analyzed by considering the perspective of compliance with applicable oil and gas law regulations, which are part of the legal framework regulated by the 1945 Constitution and support state sovereignty in managing natural resources. Through literature analysis and case studies of the oil and gas industry in Indonesia, this research aims to provide a deeper understanding of the potential use of IoT technology in the oil and gas industry in Indonesia and its implications for compliance with oil and gas law regulations. It is hoped that the results of this research will provide valuable information for oil and gas companies, regulators, and other stakeholders in formulating effective marketing strategies and complying with applicable regulations. In addition, this research also has the potential to become the basis for further research in this field. By understanding and applying IoT concepts in oil and gas marketing strategies that comply with oil and gas law regulations and the principles set out in the 1945 Constitution, a more efficient, controlled, and sustainable oil and gas industry can be created in Indonesia.